Psychosocial factors at work and sickness absence: Results from the French National SUMER Survey. Issue 6 (17th March 2014) - Lesuffleur, Thomas; Chastang, Jean‐François; Sandret, Nicolas; Niedhammer, Isabelle
<x xml:space="preserve">Abstract</x> Objective This study aims at exploring the associations between psychosocial work factors and sickness absence. Methods The sample from the French National Survey SUMER 2010 included 46, 962 employees. Sickness absence spells and days within the last year were studied as two outcomes. Psychosocial work factors included psychological demands, decision latitude, social support, reward, working time, and workplace violence variables. Covariates were age, occupation, economic activity, and other occupational exposures. Results For both genders, low latitude, low reward, shift work, bullying, and verbal abuse were risk factors of absence spells while long working hours were a protective factor. High demands, low support, and physical violence were risk factors for women. Low support and bullying for both genders, high demands for women, and low reward, long working hours, and physical violence for men increased absence duration. Conclusions This study highlights the importance of psychosocial work factors as risk factors of sickness absence. Am. J. Ind. Med. 57:695–708, 2014. © 2014 Wiley Periodicals, Inc.